Association Between Alcohol Consumption and Ectopic Fat in the Multi‐Ethnic Study of Atherosclerosis - Richard Kazibwe; Parag A. Chevli; Joni K. Evans; Matthew Allison; Erin D. Michos; Alexis C. Wood; Jingzhong Ding; Michael D. Shapiro; Morgana Mongraw‐Chaffin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background The relationship between alcohol consumption and ectopic fat distribution, both known factors for cardiovascular disease, remains understudied. Therefore, we aimed to examine the association between alcohol consumption and ectopic adiposity in adults at risk for cardiovascular disease. Methods and Results In this cross‐sectional analysis, we categorized alcohol intake among participants in MESA (Multi‐Ethnic Study of Atherosclerosis) as follows (drinks/day): <1 (light drinking), 1 to 2 (moderate drinking), >2 (heavy drinking), former drinking, and lifetime abstention. Binge drinking was defined as consuming ≥5 drinks on 1 occasion in the past month. Visceral, subcutaneous, and intermuscular fat area, pericardial fat volume, and hepatic fat attenuation were measured using noncontrast computed tomography. Using multivariable linear regression, we examined the associations between categories of alcohol consumption and natural log‐transformed fat in ectopic depots. We included 6756 MESA participants (62.1±10.2 years; 47.2% women), of whom 6734 and 1934 had chest computed tomography (pericardial and hepatic fat) and abdominal computed tomography (subcutaneous, intermuscular, and visceral fat), respectively. In adjusted analysis, heavy drinking, relative to lifetime abstention, was associated with a higher (relative percent difference) pericardial 15.1 [95% CI, 7.1–27.7], hepatic 3.4 [95% CI, 0.1–6.8], visceral 2.5 [95% CI, −10.4 to 17.2], and intermuscular 5.2 [95% CI, −6.6 to 18.4] fat but lower subcutaneous fat −3.5 [95% CI, −15.5 to 10.2]). The associations between alcohol consumption and ectopic adiposity exhibited a J‐shaped pattern. Binge drinking, relative to light‐to‐moderate drinking, was also associated with higher ectopic fat. Conclusions Alcohol consumption had a J‐shaped association with ectopic adiposity. Both heavy alcohol intake and binge alcohol drinking were associated with higher ectopic fat.